2015
DOI: 10.1007/s00253-015-7015-1
|View full text |Cite
|
Sign up to set email alerts
|

Design and preparation of quantum dots fluorescent probes for in situ identification of Microthrix parvicella in bulking sludge

Abstract: A series of quantum dots (QDs) fluorescent probes for the in situ identification of Microthrix parvicella (M. parvicella) in bulking sludge were designed and prepared. In the preparation of CdTe/CdS QDs, the 11-mercaptoundecanoic acid (11-acid) and 16-mercaptohexadecanoic acid (16-acid) were used as the stabilizer. The prepared QDs probes were characterized by Fourier transform infrared (FT-IR), X-ray diffraction (XRD), and transmission electron microscopy (TEM), and the results showed that the CdTe/CdS QDs fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 48 publications
(44 reference statements)
0
5
0
Order By: Relevance
“…NaHTe solution was prepared according to a reported method [21][22][23][24][25]. Simply, tellurium powder (0.5 mmol) and 1.5 mmol of NaBH 4 were loaded into a three-necked flask and 5 mL deionized water added.…”
Section: Synthesis Of Nahte Solutionmentioning
confidence: 99%
“…NaHTe solution was prepared according to a reported method [21][22][23][24][25]. Simply, tellurium powder (0.5 mmol) and 1.5 mmol of NaBH 4 were loaded into a three-necked flask and 5 mL deionized water added.…”
Section: Synthesis Of Nahte Solutionmentioning
confidence: 99%
“…Reviewing the literature, it was found that the toxicity of the tellurite occurs via the two probable mechanisms: i) replacing the sulfur group in a number of amino acids and as a result creating non-functional proteins and ii) severely oxidizing the glutathione reservoir of the cells, which lead to the generation of excessive amounts of reactive Shakibaie M et al oxygen species (ROS) disrupting cell macromolecules involved in metabolic pathways (5,6). Recently, tellurium has been applied in the development of novel materials such as fl uorescent CdTe quantum dots (7,8) and diff erent telluride nanostructures (9), tellurium containing nanoparticles (NPs) (10), and tellurium nanotubes (11), which may fi nd potential applications in the electronics and medicine as a new fi eld of nanotechnology approaches.…”
Section: Introductionmentioning
confidence: 99%
“…The process is in accordance with M. parvicella transport of fatty acids reported by McIlroy [ 20 ]. According to Fei [ 32 ], the quantum dots probe can only identify M. parvicella filaments protruding from the flocs and free ones in the activated sludge, but it cannot label M. parvicella inside the flocs. The quantum dots probe is nano level in size, and bigger than the fluorescent molecule probes, which makes it difficult for the quantum dots probe to penetrate the sludge flocs which are composed of bacterial aggregation.…”
Section: Discussionmentioning
confidence: 99%